Surveillance without silos: a One Health data imperative for avian influenza in West Africa - Emmanuel Musa; Francis Akpa; Godfred O. Boateng (Frontiers in Cellular and Infection Microbiology, 2026)
Highly pathogenic avian influenza (HPAI) has circulated in West Africa since Nigeria’s first human case in 2006, making the region a key entry point and dispersal hub for multiple virus lineages in sub-Saharan Africa. The 2.3.4.4b virus clade driving the global spread of avian influenza is now infecting mammals more often, a troubling sign that raises the risk of a future pandemic. At the same time, West Africa’s ability to control HPAI is held back by fragmented surveillance systems. Animal, human and environmental health services operate in isolation, rely on incompatible data formats and are managed by separate institutions, which undermines early detection and rapid response. This paper describes the existing surveillance silos in West Africa and outlines the consequences of failing to integrate them, including delayed detection of future human or animal health threats. It highlights emerging examples of One Health surveillance efforts in Nigeria, Senegal, Guinea, Benin and Ghana. From an operational standpoint, five conditions are essential for early warning and timely response: interoperable health information systems; shared governance across sectors; sustainable financing; strong communication with poultry-keeping communities; and effective cross-border collaboration. Establishing fully integrated, system-wide national surveillance platforms is indispensable for effective preparedness. Without such integration, West African countries will continue to detect and respond to emerging health threats too late. Given the region’s recurrent zoonotic spillover and expanding ecological vulnerabilities, embedding data integration at the core of preparedness strategies is essential for mitigating the risk of future pandemics.